2020
DOI: 10.1097/ccm.0000000000004473
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Coronavirus Disease 2019 Patients With Mechanical Ventilation: A Nationwide Study in China*

Abstract: Objectives: The outbreak of coronavirus disease 2019 is becoming a worldwide pandemic. Mechanical ventilation is lifesaving for respiratory distress, this study was designed to delineate the clinical features of the coronavirus disease 2019 patients with mechanical ventilation from a national cohort in China. Design: Prospective observational study. Setting: The rapid spread of severe acute respiratory syndrome coronavirus 2 has infected more than 7.7 million people and caused more than 423,000 deaths. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 10 publications
4
23
1
3
Order By: Relevance
“…This finding is similar to the results from a nationwide study conducted in China, where they reported elevated D-dimer on admission suggested a greater likelihood of invasive mechanical ventilation. The percentage of patients in the invasive and non-invasively ventilation groups with elevated D-dimer levels on admission were slightly different from our study, with a higher percentage of our subjects having elevated D-dimer levels (75.7% vs 66.7% in the invasive group and 69.1% vs 44.6% in the non-invasive group respectively) [11].…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…This finding is similar to the results from a nationwide study conducted in China, where they reported elevated D-dimer on admission suggested a greater likelihood of invasive mechanical ventilation. The percentage of patients in the invasive and non-invasively ventilation groups with elevated D-dimer levels on admission were slightly different from our study, with a higher percentage of our subjects having elevated D-dimer levels (75.7% vs 66.7% in the invasive group and 69.1% vs 44.6% in the non-invasive group respectively) [11].…”
Section: Discussioncontrasting
confidence: 93%
“…LDH was also found to be significantly elevated on admission in patients that required invasive ventilation and was the second most effective predictor of mortality after D-dimer. Studies conducted in China and Korea support our results of LDH as an effective predictor of the need for invasive ventilation in COVID-19 patients [11,12]. When looking at the elevated levels of LDH on admission in the invasive and non-invasive groups, the percentage of patients in our study was 81.4% and 69.6% respectively.…”
Section: Discussionsupporting
confidence: 84%
“…Many studies [8,9,12,13] have investigated the clinical, laboratory and radiological features of confirmed symptomatic COVID-19 patients. However, there is little attention given to the follow-up of recovered patients.…”
Section: Introductionmentioning
confidence: 99%
“…При этом большинство случаев инфицирования медицинских работников произошло на ранней стадии вспышки COVID-19, поскольку в то время еще отсутствовала информация о высокой контагиозности коронавирусной инфекции и, следовательно, индивидуальная защита являлась недостаточной. При использовании СИЗ инфицирования медицинских работников можно избежать даже при работе с пациентами с НВЛ, о чем свидетельствовали лишь единичные случаи заражения медицинских работников в более поздний период пандемии [37]. Таким образом, при работе с НВЛ риск контаминации вирусными инфекциями сводится к минимуму при адекватном использовании СИЗ.…”
Section: биоаэрозоли и защита медицинских работниковunclassified
“…К сожалению, сегодня нет надежных маркеров прогрессирования заболевания на фоне проведения НВЛ. В исследовании W.Wang et al, описывающем общенациональную когорту критически больных COVID-19 в Китае, повышенный уровень D-димера (> 1,5 мг / л) при поступлении был индикатором высокой вероятности подключения к ИВЛ [37]. Эти результаты согласуются с данными о том, что повышение уровня D-димера у пациентов с COVID-19 связано с прогрессированием заболевания [68].…”
Section: таблица 3 исследования по эффективности неинвазивной вентиляunclassified